TRANSLATION STUDY OF REFUSAL STRATEGY IN BEAUTIFUL MALICE NOVEL (A PRAGMATIC APPROACH) - Wyut Yee Soe (Universitas Sebelas Maret, 2018)
The study aims to know translation technique and translation quality of refusal strategy in Beautiful Malice novel. It was descriptive qualitative method with embedded case study. The data were obtained through content analysis and focus group discussion. They were then analyzed into domain, taxonomy and componential analysis to formulate cultural theme. The result shows that writer uses indirect and direct refusal strategy in which indirect one is mostly used. Besides, translator transfers those refusal strategies by using established equivalence, modulation, explicitation, variation, implicitation, pure borrowing, reduction, addition, addaptation, and paraphrase in which established equivalent is most frequently used. With using those techniques, the study indicates that translation quality is very good. They are 2.8 of accuracy and 2.9 of acceptability and readablity. Imperfection of translation quality is affected from the use of reduction and addition in relation to accuracy and the use of deletion in relation to those aspects of translation quality.